2019
DOI: 10.3354/meps13075
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and eco-physiological responses of the mussel Mytilus galloprovincialis to acidification and distinct feeding regimes

Abstract: The carbon dioxide taken up by the ocean is increasing as levels of atmospheric carbon dioxide increase, thus lowering the ocean pH and altering the carbonate system. In this laboratory study, we evaluated the physiological responses of juvenile mussels (Mytilus galloprovincialis) from Galician waters (NW Iberian Peninsula) exposed to control (500 µatm) and elevated (800 or 1200 µatm) seawater pCO2 conditions under two different feeding regimes (optimal and suboptimal). Shell properties such as compressive str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…Any strategy that can cope with decreased seawater pH or any other stress factor will be energetically demanding. The energetic costs of both biomineralization and byssogenesis processes are consistent with relatively higher maintenance ranges, and extra stressors such as food scarcity may further exacerbate the negative impact of OA ( Melzner et al , 2011 ; Mackenzie et al , 2014 ; Lassoued et al , 2019 ).…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Any strategy that can cope with decreased seawater pH or any other stress factor will be energetically demanding. The energetic costs of both biomineralization and byssogenesis processes are consistent with relatively higher maintenance ranges, and extra stressors such as food scarcity may further exacerbate the negative impact of OA ( Melzner et al , 2011 ; Mackenzie et al , 2014 ; Lassoued et al , 2019 ).…”
Section: Introductionmentioning
confidence: 83%
“…The pH was measured by the spectrophotometric method described by Clayton and Byrne (1993 ). More detailed information about the analytical methods is provided in a previous article ( Lassoued et al , 2019 ). Calculations were carried out using the equations proposed by Dickson et al (2007 ), who included a correction factor for the difference between seawater and the acidity indicator.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clumping behaviour in Mytilus edulis (Kong et al, 2019) was affected by acidification; however multiple studies suggest no effect on baseline valve gaping activity in marine bivalves, even under extremely low pH conditions (pH < 7) (Bamber & Westerlund, 2016;Clements et al, 2018;Jakubowska & Normant, 2015). Furthermore, while valve gaping in Mytilus galloprovincialis was affected by acidification when food was reduced, normal feeding regimes saw no effect (Lassoued et al, 2019). While it could be argued that the lack of pH effect is due to the cue type used (i.e., tactile versus olfactory), a recent study on Mytilus galloprovincialis found no effect of low pH on valve closure responses to chemical alarm cues ..…”
Section: Effects Of Elevated Temperature and Low Phmentioning
confidence: 98%